PENGARUH IMPLEMENTASI DIRECT INSTRUCTION DENGAN STRATEGI MATHEMATICAL WORKING SPACE TERHADAP PENCAPAIAN KEMAMPUAN KONEKSI, BUKTI, DAN KONSEP DIRI MATEMATIS MAHASISWA CALON GURU MATEMATIKA - Muchamad Subali Noto, - (2022)
The ability of connection and mathematical proof is needed in learning transformation geometry, but in fact this mathematical ability is still low. This study aims to analyze and comprehensively study the achievement of mathematical connection abilities (MCA), mathematical proof abilities (MPA), and mathematical self-concepts (MSC) of students who received direct instruction learning with mathematical working space (DI-MWS) strategies and conventional learning (CL) in terms of the overall and Prior Mathematical Knowledge (PMK) of students (high, medium, low) in the transformation geometry material. In addition, to analyze the interaction effect between learning (DI-MWS and CL) and PMK on the achievement of student MCA and MPA. The research method used is a quasi-experimental research design with post-test only control group design. The research subjects were students of the Mathematics Education Study Program at one of the universities in the city of Cirebon with 41 subjects selected purposively. Data analysis was carried out quantitatively on posttest data to see achievement, and questionnaire data to see mathematical self-concept. The results show that: 1) The MCA achievement of the students who studied at DI-MWS is better than the MCA of the students who received conventional learning, this happens to the students with moderate PMK; 2) There is no interaction effect between learning factors (DI-MWS and CL) and student PMK factors on the achievement of MCA; 3) The MPA achievement of the students who received DI-MWS is better than those who received CL; 4) There is no interaction effect between learning factors (DI-MWS and CL) and student PMK factors on the achievement of MPA; and 5) MCS achievement of the students who received DI-MWS is better than those who received CL.